Constructions prompting communicative behaviours: perception and attention in the development of metalinguistic awareness in children - Navarro Ciurana, David (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Metalinguistic awareness involves attentional control of communicative behaviours and a distancing from language as a vehicle of communication. Its early development in the child requires, firstly, a perception of language as an object of reference and, subsequently, the ability to fixate attention on it through inhibitory action. From a usage-based approach, we consider that this ability emerges through input, so in this paper we examine collaborative strategies of language stimulation between caregiver and child, which we refer to as communicative behaviour-triggering constructs. Based on the analysis of two longitudinal corpora of infant speech, we show the role that such constructions play in the development of metalinguistic awareness, through the triangulation of joint attention to language as an object. Finally, productive and creative uses of this type of constructions are analysed, which demonstrate a high level of metalinguistic control at an early age.